PENGARUH SARANA DAN PRASARANA TERHADAP EFEKTIVITAS KERJA PEGAWAI DI DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN SUMEDANG - Irma Hermayanty (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2017)
The purpose of research that researchers do is to determine the effect of facilities and infrastructure on the effectiveness of employees in the Office of Population Control and Family Planning Sumedang District and to determine the relationship between facilities and infrastructure with the effectiveness of employees in the Office of Population and Family Planning Sumedang District. The method used in this study is a quantitative research method which is used in research based on positivism philosophy with the aim to test the hypothesis that has been set. In this study researchers used inferential descriptive data analysis techniques describe or describe the data that has been collected as is by making conclusions that apply to the public. The sampling technique used in this study is the technique of proportional stratified random sampling, with a population of 36 people then the researchers used the Slovin formula to obtain the sample to 26 respondents. Based on the results of the study, research can illustrate that the procurement of facilities and infrastructure carried out by the Department of Population and Family Planning Sumedang District has reached 69.42% and the numbers are categorized Good, as well as with the effectiveness of employees of the Office of Population Control and Family Planning Sumedang District reached 70.77% and the numbers are categorized Good. The relationship of facilities and infrastructure with the effectiveness of employees of the Office of Population Control and Family Planning Sumedang District with a correlation coefficient of 0.993 is in the category very strong. While the influence of facilities and infrastructure to the effectiveness of employees of the Office of Population Control and Family Planning Sumedang District reached 98.6% of the rest of 1 .4% influenced by other factors not investigated by researchers called the epsilon factor.